STRATEGI UMKM BERTAHAN BERTAHAN DIMASA PANDEMI COVID 19 - Wasil, Mohammad (Pusat Studi GESI - UWP, 2023)
This study aims to analyze the strategies implemented by MSMEs to survive during the COVID-19 pandemi. In this uncertain situation, MSMEs need to adopt the right strategy in order to counteract the negative impact of the pandemi and ensure the continuity of their operations. Various strategies that have been successfully implemented include developing innovative marketing, utilizing digital technology, customizing products and services, and increasing competitive advantage. In addition, support from the government and access to assistance and necessary resources are also important factors in MSMEs' efforts to survive. This study provides important insights for MSMEs and other stakeholders in dealing with the challenges faced during the COVID-19 pandemi and provides recommendations for effective strategies to maintain MSME business continuity in times of crisis.